Collective properties of injection‐induced earthquake sequences: 2. Spatiotemporal evolution and magnitude frequency distributions. Issue 5 (20th May 2016) - Dempsey, David; Suckale, Jenny; Huang, Yihe
Abstract: Probabilistic seismic hazard assessment for induced seismicity depends on reliable estimates of the locations, rate, and magnitude frequency properties of earthquake sequences. The purpose of this paper is to investigate how variations in these properties emerge from interactions between an evolving fluid pressure distribution and the mechanics of rupture on heterogeneous faults. We use an earthquake sequence model, developed in the first part of this two‐part series, that computes pore pressure evolution, hypocenter locations, and rupture lengths for earthquakes triggered on 1‐D faults with spatially correlated shear stress. We first consider characteristic features that emerge from a range of generic injection scenarios and then focus on the 2010–2011 sequence of earthquakes linked to wastewater disposal into two wells near the towns of Guy and Greenbrier, Arkansas. Simulations indicate that one reason for an increase of the Gutenberg‐Richter b value for induced earthquakes is the different rates of reduction of static and residual strength as fluid pressure rises. This promotes fault rupture at lower stress than equivalent tectonic events. Further, b value is shown to decrease with time (the induced seismicity analog of b value reduction toward the end of the seismic cycle) and to be higher on faults with lower initial shear stress. This suggests that faults in the same stress field that have different orientations, and therefore different levels of resolved shear stress, should exhibit seismicity with different b ‐values. A deficit of large‐magnitude events is noted when injection occurs directly onto a fault and this is shown to depend on the geometry of the pressure plume. Finally, we develop models of the Guy‐Greenbrier sequence that captures approximately the onset, rise and fall, and southwest migration of seismicity on the Guy‐Greenbrier fault. Constrained by the migration rate, we estimate the permeability of a 10 m thick critically stressed basement fault to be 5 × 10 −12 m 2 . We also consider alternative scenarios in which only one of the two disposal wells operated and suggest that, due to the wells interacting, total seismicity may be greater than that attributable to each well alone. Key Points: Induced seismicity b value evolution reflects modification of underlying rupture energy physics Deficit of induced large‐magnitude events due to a plume shape effect Guy, AR seismicity model of rate, migration, nonlinear GR distribution; invert fault permeability